2015
DOI: 10.1002/biot.201400841
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic vectors for gene delivery: An overview of their evolution depending on routes of administration.

Abstract: Nucleic acid delivery constitutes an emerging therapeutic strategy to cure various human pathologies. This therapy consists of introducing genetic material into the whole body or isolated cells to correct a cellular abnormality or disfunction. As with any drug, the main objective of nucleic acid delivery is to establish optimal balance between efficacy and tolerance. The methods of administration and the vectors used are selected depending on whether the goal of treatment is the production of an active protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 166 publications
1
30
0
Order By: Relevance
“…Gjetting et al have reported that addition of 10% PEG to lipoplexes caused a reduced retention in heart tissues of nude mice in comparison with unpegylated lipoplexes [ 39 ]. These observations were in accordance with our previous BFI imaging ( Figure 5 A,B), and confirmed the benefit of pegylation to enhance the in vivo bioavailability of complexes [ 30 , 42 , 44 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Gjetting et al have reported that addition of 10% PEG to lipoplexes caused a reduced retention in heart tissues of nude mice in comparison with unpegylated lipoplexes [ 39 ]. These observations were in accordance with our previous BFI imaging ( Figure 5 A,B), and confirmed the benefit of pegylation to enhance the in vivo bioavailability of complexes [ 30 , 42 , 44 ].…”
Section: Resultssupporting
confidence: 92%
“…Thus, different cationic lipids such as lipophosphonates [ 15 , 16 , 17 ] and lipophosphoramidates [ 12 , 13 , 18 , 19 , 20 , 21 ] have been produced, and their high ability to transfect cells in culture and lungs mice were demonstrated [ 13 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, the plasmid type [ 27 , 28 , 29 ], the vector [ 18 , 26 , 29 , 30 , 31 , 32 ] as well as the nucleic acids (NA) or synthetic carrier’s labeling techniques [ 8 , 30 , 33 , 34 , 35 ], impact greatly the distribution in tissues as well as the transgene expression. Labeling liposomes with a fluorescent probe appears as a relevant procedure to establish biodistribution profiles of lipoplexes and their pharmacokinetics, irrespective of administration route [ 26 , 27 , 31 , 32 , 33 , 34 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cationic liposomes have been classified as one of the most attractive nanocarriers for small interference RNA (siRNA) delivery [ 1 , 2 , 3 ]. The RNA interference (RNAi) mechanism induced by siRNA holds high interest in treating human diseases—especially in cancers—since siRNA can selectively target and repress a specific gene associated with pathologies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…lamellar versus hexagonal). For nucleic acids delivery, cationic amphiphiles [2,13,14] were evaluated for different purposes (lung transfection, [15,16] tendon healing, [17] cancer therapy, [18] anticancer vaccination [19][20][21] ) and the current developments offer news therapeutic perspectives. It must be emphasized that one of the interest of synthetic vectors, when compared to viral vectors, is that they can be produced on large scale and following simple purification processes.…”
Section: Introductionmentioning
confidence: 99%